Poetic activism in contemporary Argentina (Revista de Crítica Literaria Latinoamericana, 2012)
Much has been written on the emergence of new forms of artistic and film production in Argentina in the 2000s, in particular collective and/or innovative means of production in the "post-crisis". We propose a reading of poems by poet-activists —Arturo Carrera, Washington Cucurto, and Sergio Raimondi— in order to examine the coherence, or otherwise, between activism and poetics.
Keywords: Argentina; poetic activism; post-crisis; cultural studies